Влияние глубины отверстия на силу резания и условия транспортирования стружки при глубоком безвыводном сверлении алюминиев - Маршуба, Вячеслав Павлович; Плахотникова, И. Б. (НТУ "ХПИ", 2005)
The influence of aperture’s drilling depth for one passing on cutting force and conditions of boring transporta-tion is investigated at peck feed drilling of linear aluminum alloys on multihued machines. On the basis the obtained relationships for the changing of cutting force and conditions of boring transportation under given working environ-ment, the ways removing negative consequences of process of peck feed drilling are developed. The usage of these rela-tionships will allow determining the necessary conditions for processing of apertures with maximum productivity while processing of details from these alloys.
Keywords: обработка механическая; инструмент режущий; сила трения; адгезия